2006
DOI: 10.1002/ijc.22367
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor receptor superfamily member TROY is a novel melanoma biomarker and potential therapeutic target

Abstract: Incidence of melanoma continues to rise, and a better understanding of its genetics will be critical to improve diagnosis and develop new treatments. Here, we search for novel melanoma-specific genes that may serve as biomarkers and therapeutic targets by using an in vitro genetic screen. One identified cDNA encoded TROY, a member of the tumor necrosis factor receptor superfamily (TNFRSF). TROY is widely expressed during embryogenesis, but in adults expression is restricted to hair follicles and brain. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…The tightly regulated expression of TROY suggests that alterations in TROY expression may have undesirable effects on cell proliferation and migration. This suggestion is supported by the demonstration that TROY is highly expressed in primary and metastatic melanoma cells but not in normal melanocytes (35). A recent study demonstrated that TROY expression is significantly upregulated in tumor infiltrating microglia in GBM and is involved in the regulation of their migration (36).…”
Section: Discussionmentioning
confidence: 85%
“…The tightly regulated expression of TROY suggests that alterations in TROY expression may have undesirable effects on cell proliferation and migration. This suggestion is supported by the demonstration that TROY is highly expressed in primary and metastatic melanoma cells but not in normal melanocytes (35). A recent study demonstrated that TROY expression is significantly upregulated in tumor infiltrating microglia in GBM and is involved in the regulation of their migration (36).…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, the combination of PPF and TMZ or radiation resulted in a significant decrease in survival compared to single-agent therapy alone, suggesting synergism between pharmacological inhibition of TROY and treatment with cytotoxic agents. TROY has also been implicated in the pathogenesis of other tumors, which suggests inhibition of TROY may be a therapy in other malignancies [12,11]. Together, these results suggest that PPF may be a potential adjuvant medication that will increase tumor vulnerability and garner improved therapeutic response in patients.…”
Section: Discussionmentioning
confidence: 98%
“…TROY is expressed in multiple cell lineages during embryogenesis, but its expression is restricted to the hair follicles and brain postnatally [79]. TROY is a susceptibility factor in nasopharyngeal carcinoma and metastatic lung cancer and its expression has been linked to the pathogenesis of multiple human malignancies [1012]. In GBM, TROY overexpression activates Rac1 signaling in a Pyk2-dependent manner to drive migration and invasion [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, TROY was reported to be a β-catenin target gene and to form a complex with LGR5 in cellular membranes (13). Although overexpression of TROY is observed in CRC cell lines (14)(15)(16)(17), its clinical significance for CRC is poorly understood. Because TROY might be a possible prognostic biomarker of CRC, we performed this study to investigate the clinical significance of TROY in patients with CRC and compared its clinical usefulness to that of LGR5.…”
Section: Introductionmentioning
confidence: 99%